The Use of Acronyms in Study Courses: a Linguistic Research in Tanjungpinang - Cahyani, Raden Roro Priscylla Dwi; Askurny, Nana Raihana; Melvina, Rere; Wulandari, Tiara Aprillia; Fatika, Sandia; Elvitriana, Elvitriana; Andri, Andri (Jurnal Sasindo UNPAM, 2025)
This research examines the use of acronyms in naming non-formal education institutions, specifically course institutions, in Tanjungpinang City as part of the urban linguistic landscape.. Using a descriptive qualitative approach, data was obtained through observation and visual documentation of publicly visible signage of primary and secondary educational institutions. The collected data were then analyzed thematically to identify patterns in acronym usage and their symbolic meanings.  The results show that acronyms are used not only for linguistic efficiency, but also as a branding strategy that represents a professional, modern and global identity. The majority of acronyms consist of three to four letters and are dominated by English, reflecting the institution's international orientation. This prominence of English acronym in Tanjungpinang’s educational landscape underscores a growing global outlook and a strategic effort to enhance institutional recognition and apple beyond local boundaries. However, without additional explanation, the use of acronyms as branding tools can cause ambiguity and weaken their function as identity markers. . Therefore, the integration of visual elements and descriptive captions is essential for acronyms to be effective as identification and marketing tools. These findings enrich the study of the linguistic landscape in the context of non-formal education in Tanjungpinang.